Yoshida Ami’s Onkyō and the Persistently "Japanese" Body: Making (Electro)voice Sound - Jude, Gretchen (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
This essay examines the experimental vocal and electronic work of Yoshida Ami in the context of the Japanese onkyō movement of the turn of the millennium, developing the concept of “plasmatic voice” that addresses the assemblage of embodied vocal performance through audio technology. Understanding vocal performance as it circulates globally through digital media networks must be perforce include transcultural analysis of race, culture, and gender, as well as other salient identity categories dependent on context. The essay also closely examines common metaphors for audio devices (such as microphones) as part of a programmatic attempt to listen deeply to human and nonhuman sounding without relying on the normative human body as the centre of analysis. Instead, a process-based approach following Jasbir Puar’s combining of intersectionality alongside assemblage theory is undertaken.